Flavodiiron proteins associate pH-dependently with the thylakoid membrane for ferredoxin-1-powered O2 photoreduction - Nikkanen, Lauri; Vakal, Serhii; Hubáček, Michal; Santana-Sánchez, Anita; Konert, Grzegorz; Wang, Yingying; Boehm, Marko; Gutekunst, Kirstin; Salminen, Tiina A.; Allahverdiyeva, Yagut (WILEY, 2026)
Flavodiiron proteins (FDPs) catalyse light-dependent reduction of oxygen to water in photosynthetic organisms, creating an electron sink on the acceptor side of Photosystem I that protects the photosynthetic apparatus. However, ambiguity about the electron donor(s) remains, and the molecular mechanisms regulating FDP activity have remained elusive.
We employed spectroscopic and gas flux analysis of photosynthetic electron transport, bimolecular fluorescence complementation assays for in vivo protein-protein interactions in the model cyanobacterium Synechocystis sp. PCC 6803, and in silico surface charge modelling.
We demonstrated that ferredoxin-1 interacts with Flv1, Flv2, and Flv3, and is the main electron donor to FDP heterooligomers, which are responsible for the photoreduction of oxygen. Moreover, we revealed that FDP heterooligomers dissociate from the thylakoid membrane upon alkalisation of the cytosol, providing the first in vivo evidence of a self-regulatory feedback mechanism allowing dynamic control of FDP activity and maintenance of photosynthetic redox balance in fluctuating environments.
Our findings have direct implications for rationally directing electron flux towards desired reactions in biotechnological applications.